Formulation of Conventional Herbal Tablets Based on Lempuyang Wangi, Daun Pegagan, Adas Manis and Temulawak for Weight Gain - Ratu, Renike Lyana Monalisa; Suwitono, Marvel Reuben; Sulastri, Titin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
There are many medicinal plants in Indonesia and people have used these medicinal plants to overcome health problems. Tablets are usually made by mixing these ingredients, then pressing the mixture into a solid and easy-to-take form. This study aims to develop a conventional tablet formulation from herbal extracts of Lempuyang Wangi, Pegagan Leaves, Sweet Fennel and Temulawak to increase weight gain. Data were analyzed by conducting granule testing. The results showed that the developed tablet formulation met the requirements for weight uniformity and disintegration time. However, the hardness of the tablet was still below standard. This study shows the potential for further development of this herbal tablet formulation by optimizing the amount and type of binder. The conclusion is that herbal tablets can increase body weight, but optimization of the formulation is still needed.